CONCEPTUAL UNDERSTANDING AND PROBLEM-SOLVING SKILLS: THE IMPACT OF HYBRID LEARNING ON MECHANICS - Yessi Affriyenni; Arif Hidayat; Galandaru Swalaganata (Universitas Bhinneka PGRI, 2020)
Mechanics is a challenging topic not only for the students majoring in physics but also for those who are not majoring in physics. This study aims to discover the correlation between students’ conceptual understanding and problem-solving skills experienced by students who major in natural science. The analysis was conducted after the course had been delivered using the hybrid-learning method. Students’ conceptual understanding was measured using 13 multiple-choice questions while their problem-solving skill was measured using 3 essay questions. The normality, the linearity, and the correlation of the data were analyzed. The data is normally distributed with the average score of students’ conceptual understanding was 83 and the average score of students’ problem-solving skills was 48. The linearity test shows that there is a significant linear correlation between students’ conceptual understanding and problem-solving skills. However, the Pearson Correlation test result shows that there is no significant positive correlation between the two variables with the coefficient of determination was only 15.4%.